Lap shear strength of nanofillers modified epoxy adhensives - Poon, Yvette Qi Ying. (2011)
Epoxy adhesives are very versatile and have a wide range of applications. These include coatings, adhesives and composite materials. Due to the unique chemistry of epoxies and the range of existing variations available in the market, epoxies with a broad range of properties can be readily synthesized. As such, epoxies are known for their excellent adhesion, chemical and heat resistance and good mechanical properties, they are very much favored for aerospace applications. However, epoxy adhesives have low lap shear strength at elevated temperatures. As such, nanoparticles are dispersed into epoxy adhesives to improve their lap shear strength. This project aims to further understand the effects that diluting different percentages of silica nanoparticles into epoxy adhesives will have on their mechanical single – lap shear strength. In this project, silica nanoparticles with an average diameter of 20nm were used and it was found that the optimal filler content is 0.5 wt%. Other factors such as the thickness of the epoxy adhesive, type of pretreatment used and also the strain rate during testing were studied. It was found that using a thinner layer of epoxy adhesive generally gave rise to higher lap shear stress. Two different types of pretreatment was used; BR 127 Corrosion Inhibiting Primer and (3-Glycidyloxypropyl) trimethoxysilane. It was found that using BR 127 Primer allows higher lap shear stress as compared to using (3-Glycidyloxypropyl) trimethoxysilane. In addition, a general trend exists whereby the mechanical strength of the single – lap shear strength increases as the loading speed increases.